Effectiveness of tonsillectomy in periodic fever, aphthous stomatitis, pharyngitis, and cervical adenitis syndrome: a case series - Kazuto Taniguchi; Sakumo Kii; Kazuyasu Uemichi (Indonesian Pediatric Society, 2021)
Periodic fever, aphthous stomatitis, pharyngitis, and cervical adenitis (PFAPA) syndrome is characterized by periodic high fever (febrile attacks) lasting for 3–6 days and recurring regularly. In this syndrome, fever is associated with aphthous stomatitis, pharyngitis, and cervical adenitis.1-4 Almost all patients with PFAPA syndrome spontaneously resolve approximately 8 years after the onset of symptoms. However, the cause and etiology of PFAPA syndrome remain unclear.4 Oral prednisolone reduces fever during febrile attacks.5-7 Tonsillectomy has also been reported to induce remission of PFAPA syndrome.8-12 However, tonsillectomy is not a popular treatment for PFAPA syndrome because its effectiveness is still unclear. Furthermore, tonsillectomy is generally recommended for patients aged 3 years and older to avoid post-operative complications.13 We report here on four patients aged 3 years and older with PFAPA syndrome. Tonsillectomy completely eliminated febrile attacks and was safely performed without post-operative complications in all of our patients.